Radiation-induced miR-208a increases the proliferation and radioresistance by targeting p21 in human lung cancer cells. Issue 1 (December 2016) - Tang, Yiting; Cui, Yayun; Li, Zengpeng; Jiao, Zhuqing; Zhang, Yong; He, Yan; Chen, Guangxia; Zhou, Qunyan; Wang, Wenjie; Zhou, Xifa; Luo, Judong; Zhang, Shuyu
Abstract Background Lung cancer has long been the most dangerous malignant tumor among males in both well developed and poorly developed countries. Radiotherapy plays a critical role in the curative management of inoperable non-small cell lung cancer (NSCLC) and is also used as a post-surgical treatment in lung cancer patients. Radioresistance is an important factor that limits the efficacy of radiotherapy for NSCLC patients. Increasing evidence suggests that microRNAs (miRNAs) possess diverse cellular regulatory roles in radiation responses. Methods In this study, we used miRNA microarray technology to identify serum miRNAs that were differentially expressed before and after radiotherapy in lung cancer patients. We further examined the biological function of miR-208a on cell viability, apoptotic death and cell cycle distribution in human lung cancer cells and explored the probable mechanism. Results Nine miRNAs, including miR-29b-3p, miR-200a-3p, and miR-126-3p were significantly down-regulated, whereas miR-208a was the only miRNA that was up-regulated in the serum of the patients after radiation treatment (P  < 0.05). The expression of miR-208a could be induced by X-ray irradiation in lung cancer cells. Forced expression of miR-208a promoted cell proliferation and induced radioresistance via targeting p21 with a corresponding activation of the AKT/mTOR pathway in lung cancer cells, whereas down-regulation of miR-208a resulted in the opposite effects. In addition, down-regulation of miR-208a increased the percentage of cells undergoing apoptosis and inhibited the G1 phase arrest in NSCLC cells. Moreover, miR-208a from the serum exosome fraction of lung cancer patients could shuttle to A549 cells in a time-dependent manner, which was likely to contribute to the subsequent biological effects. Conclusions The present study provides evidence that miR-208a can affect the proliferation and radiosensitivity of human lung cancer cells by targeting p21 and can be transported by exosomes. Thus, miR-208a may serve as a potential therapeutic target for lung cancer patients.